2021
DOI: 10.1111/clr.13704
|View full text |Cite
|
Sign up to set email alerts
|

How old is old for implant therapy in terms of implant survival and marginal bone levels after 5–11 years?

Abstract: Aim To evaluate implant survival and marginal bone levels (MBLevel) at least 5 years after implant installation in patients ≥65 years old. Methods Patient records were screened retrospectively for the following inclusion criteria: (1) ≥65 years of age at the time of implant installation, and (2) ≥5‐year radiographic follow‐up or registered implant loss. Association between patient‐ and implant‐related data with radiographically assessed data [i.e. implant survival, mean MBLevel (i.e. average of mesial and dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…This study evaluated the survival rate of implants after the use of ISFDPs, meaning that all implants included in this study had achieved osseointegration successfully. These findings support previous studies that suggested that ISFDPs are a predictable long-term treatment option in the elderly population [ 13 , 14 , 15 , 16 ]. Eight of the eleven lost implants were due to peri-implantitis and one implant was lost due to bone resorption without inflammation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study evaluated the survival rate of implants after the use of ISFDPs, meaning that all implants included in this study had achieved osseointegration successfully. These findings support previous studies that suggested that ISFDPs are a predictable long-term treatment option in the elderly population [ 13 , 14 , 15 , 16 ]. Eight of the eleven lost implants were due to peri-implantitis and one implant was lost due to bone resorption without inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…In general, previous reports have proven that dental implant treatments for partially or completely edentulous patients could be a solution to declined oral function and poor aesthetics [ 6 , 7 , 8 , 9 , 10 ]. Although aging exerts a certain effect on systemic and oral health [ 11 , 12 ], previous studies have shown that aging alone does not affect implant treatment and its prognosis [ 13 , 14 , 15 , 16 ]. However, aging-associated factors, such as systemic diseases, and peri-implant tissue inflammation due to a poor oral hygiene capacity might be risk factors affecting the longevity of implants [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment should be determined by the patient's health, functional needs, quality of life and not their age. Elderly patients heal in the same fashion as younger patients (17,18,19). Patients older than 80 may have less bone loss and fewer implant failures than younger patients (18,19).…”
Section: Discussionmentioning
confidence: 79%
“…The treatment process should be based on a philosophy that addresses the best interests of the patient. (14,15,16,17) The patient and clinician working in tandem decide the treatment (17,18,19). The patient is informed of the risks and benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews are currently reporting implant survival rates of about 95% up to 10 years, both for single‐tooth restorations and when supporting fixed dental prostheses (Jung et al, 2012; Pjetursson et al, 2012). These positive outcomes are basically irrespective of the patient's age (Bertl et al, 2019; Etöz et al, 2020; Schimmel et al, 2018; Srinivasan et al, 2017). Such high survival rates reflect not only the refinement of surgical techniques and treatment concepts, but also the advances in dental implant manufacturing and technologies.…”
Section: Introductionmentioning
confidence: 99%